Zakat Poverty Line Index And Urban-rural Poverty In Malaysia: A Critical Analysis - Muhammad Ridhwan Ab. Aziz; Mohd Faisol Ibrahim; Ahmad Fahme bin Mohd Ali (2024)
Pensee Journal Vol 76, No. 7;Jul 2014